Rancang Bangun Sistem Informasi Sebagai Media Promosi Untuk Usaha Mikro Kecil Menengah (UMKM) - Yonanda Aditama Sari; Ridho Pamungkas; Andria (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2021)
The use of technology in the business sector is not only for large businesses and companies that are growing rapidly, but also for UMKM. With this technology can increase the number of turnover and increase the number of customers. Previously shining UMKM had utilized information media such as Facebook and Instagram. In managing UMKM Bersinar uses Facebook and Instagram and is managed directly by the chairman of UMKM Bersinar using a personal account. Based on the results of interviews and observations of the UMKM Bersinar owners, there were several obstacles experienced during the marketing of the UMKM Bersinar product business, only Facebook and Instagram users who were friends with the UMKM Bersinar chairman who had facts about the UMKM Bersinar product.In the obstacles experienced by the UMKM Bersinar, it can be concluded that the ongoing problem is what technology can market the UMKM Bersinar product widely and thoroughly. One solution to this problem is to build a website-based marketing and promotion information system that shines UMKM need